A framework for Islamic advertising: using Lavidge and Steiner's hierarchy of effects model - Mokhtar, Aida (IIUM Press, 2016)
Lavidge and Steiner’s (1961) hierarchy of effects model has strengths in its pragmatism and clarity. It outlines the series of steps consumers take with the purchase of products being the final step. The steps are related to the cognitive, affective and conative components of psychology. Advertisers could use advertising and other marketing communication tools to spur consumers up the steps of the model. The purpose of this paper is to examine the Lavidge and Steiner model from the Islamic perspective and produce a framework of Islamic advertising. This aim arose from the targeting of the growing Muslim market by several advertising campaigns. It also arose from previous research studies that have recommend advertisers be sensitive to the Islamic beliefs of the Muslim target audience in producing effective advertising messages. The model therefore requires an Islamic dimension to guide the production of effective advertisements for Muslims.